Pengembangan Sistem Simulasi Perkiraan Penyebaran Api Pada Gunung Arjuno Kawasan Tahura R. Soerjo Menggunakan Tangible Landscape - Adhi Isti Febriandhika; Fatwa Ramdhani; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Forest fires is a condition where forests are hit by flames, causing damage of forests and or forest products that causes economic losses and environmental value. May occur naturally or prescribed, and until now the spread of fire during forest fires has not been predicted with certainty, because there is a lot of variability in fire triggering factors. East Java is a Province in Indonesia that often occurs forest fires. One of the forest areas that often occur forest fires in East Java Province is Tahura R. Soerjo area, and forest fires are one of the most difficult issues handled by Tahura R. Soerjo in managing forest areas. Until now the technology to overcome the problem of forest is still very minimal. The Tangible Landscape method can be used to simulate the possibility of spreading fire that occurs in real-time. By using Tangible Landscape and GRASS GIS, multiple fire simulation scenarios can be performed, and experimenting the determination of making different fire breaks on physical models to evaluate their effectiveness in overcoming the spread of fires. In this study the level of conformity of physical models with actual elevation data in the study area was 30% at maximum values and -28% at minimum values. The simulation process of estimating the spread of fire in this study produces data on the pattern of spread at a certain time according to the specified time and produces a data base rate of spread of 1.18 meters / minute, the maximum rate of spread is the highest of 403.99 meters / minute and the lowest amounting to 5.57 Meters / Minute, the direction of maximal rate of spread that spreads to 19 to 316 degrees in units of degree of wind direction, and maximal spotting distance of 0 to 303 meters.